Stimming behaviour in a 4-year-old girl with autism spectrum disorder - Masiran, Ruziana (BMJ Publishing Group, 2018)
A 4-year-old girl with autism spectrum disorder (ASD) developed a new behaviour of biting hard objects over the previous 6months. The behaviour has not gotten better over time and she would always explore toys made of hard material (video 1) this way. Fortunately, she has not sustained any injury, choked on or swallowed these objects. She likes hot and spicy foods with textures. Her expressive language has only developed poorly.